Higher energy conversion efficiency in anaerobic degradation of bioplastic by response surface methodology. (25th March 2021) - Ebrahimzade, Iman; Ebrahimi-Nik, Mohammadali; Rohani, Abbas; Tedesco, Silvia
Abstract: Anaerobic degradation of bioplastics is a controversial challenge. Size reduction is a must for degradation while it requires a significant amount of energy, which lowers the overall energy efficiency of the system. On the other hand, inoculum to substrate ratio has interaction effects in the process. The present work aimed to optimize these two parameters for the improvement of energy efficiency through response surface methodology. The central composite design procedure was implied. The levels of the experimental variables were 0.72, 4.3, 7.87 mm for particle size and 2, 3, and 4 for inoculum to substrate ratio. The input variable effects on biomethane yield were estimated, discussed, and then also optimized using the genetic algorithm. Moreover, energy balance analysis was done for the samples. The highest biomethane yield was found at the particle size of 4.3 mm and inoculum to substrate ratio of 4, which corresponds to 23% energy efficiency. Despite the high energy consumption for size reduction to less than 1 mm, more biomethane yield was not observed. Inoculum to substrate ratio showed more effect on biomethane yield than particle size. Highlights: The best result was for PS:4.3, ISR:4 with 23% energy efficiency. Biodegradability values varied between 42% and 78% which are considerably high. Increasing each ISR unit raised the biomethane production by approximately 20%. Reducing the PS to less than 1 mm did not have a significant effect on production. The optimal PSs were 3.21, 3.46, and 2.64 mm for ISR:2, ISR:3, ISR:4, respectively.